Review of ’The Diary of a Young Girl: The Definitive Edition’: Implications of War on Young People in the 21st Century - Aryal, Arnav (A Bi-annual South Asian Journal of Research & Innovation, 2023)
Anne Frank’s ’The Diary of a Young Girl: The Definitive Edition’ serves as a poignant reflection on the experiences of young people during World War II and offers insights into trauma and resilience among youth in contemporary war-affected regions. The diary provides a firsthand account of the Holocaust, capturing the fear, uncertainty, and emotional turmoil experienced by Jews in hiding during the war. Anne’s unwavering hope and determination shine through, offering a beacon of light amidst the darkness. This is a key theme that resonates with the ongoing experiences of young people in war-affected regions even today. Anne Frank’s story, though unique in its context, provides a lens through which to understand the enduring trauma and remarkable resilience of young people who endure the horrors of war. The diary highlights the profound psychological impact of war on young people, including the trauma of violence, displacement, and loss, as well as the disruption of education, socialization, and development. Anne’s story also exemplifies the resilience of the human spirit, as she maintains hope, optimism, and belief in the goodness of humanity despite the horrors of war. Anne Frank’s diary is a call to remember the victims of war and to work tirelessly to prevent future atrocities. It is a call to build a world where young people can grow up free from fear, violence, and oppression. We must answer this call with courage, compassion, and an unwavering commitment to creating a better future for all.